2015
DOI: 10.18632/oncotarget.4126
|View full text |Cite
|
Sign up to set email alerts
|

Metformin combined with aspirin significantly inhibit pancreatic cancer cell growthin vitroandin vivoby suppressing anti-apoptotic proteins Mcl-1 and Bcl-2

Abstract: Metformin and aspirin have been studied extensively as cancer preventive or therapeutic agents. However, the effects of their combination on pancreatic cancer cells have not been investigated. Herein, we evaluated the effects of metformin and aspirin, alone or in combination, on cell viability, migration, and apoptosis as well as the molecular changes in mTOR, STAT3 and apoptotic signaling pathways in PANC-1 and BxPC3 cells. Metformin and aspirin, at relatively low concentrations, demonstrated synergistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 61 publications
(68 reference statements)
2
73
0
Order By: Relevance
“…Bad, or the Bcl-2 associated death promoter, is a member of the pro-apoptotic Bcl-2 family, which also includes Bim, Bax, and Bid. Other studies demonstrated either no change in Bad levels (pancreatic cell lines, PANC-1 and BxPC3) [35] or an increase in Bad expression (ovarian epithelial cell lines, OVCAR-3, and OVCAR-4) [36] after metformin. In addition, we identified changes in cell-cycle markers that differ from the description of others.…”
Section: Discussionmentioning
confidence: 98%
“…Bad, or the Bcl-2 associated death promoter, is a member of the pro-apoptotic Bcl-2 family, which also includes Bim, Bax, and Bid. Other studies demonstrated either no change in Bad levels (pancreatic cell lines, PANC-1 and BxPC3) [35] or an increase in Bad expression (ovarian epithelial cell lines, OVCAR-3, and OVCAR-4) [36] after metformin. In addition, we identified changes in cell-cycle markers that differ from the description of others.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study reported that metformin combined with vemurafenib may induce apoptosis and result in the synergistic inhibition of the growth of cancer cells, suggesting that metformin reverses the resistance of cancer cells to vemurafenib by altering the cellular energy balance (24). Metformin and salicylate may synergistically reduce the survival of cancer cells in vitro by inhibiting de novo lipogenesis and targeting pro-apoptotic and Bcl-2 family members (25,26). Metformin also synergizes with chemotherapy to reverse multi-drug resistance in cancers by targeting the AMPK/mTOR/hypoxia inducible factor-1α/P-glycoprotein/multidrug resistance-associated protein 1 signaling pathway (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, metformin and aspirin have synergistic effects and share several underlying mechanisms for controlling cancer (24)(25)(26). In the present study, we investigated the antitumor activity of aspirin and metformin mediated by the TGF-β signaling pathway.…”
Section: Introductionmentioning
confidence: 98%